Determinants of Minimum Dietary Diversity Among Children Aged 6–23 Months in 7 Countries in East and Southern Africa (P10-035-19). (13th June 2019) - Kang, Yunhee; Chimanya, Kudakwashe; Matji, Joan; Garg, Aashima; Heidkamp, Rebecca; Marshal, Quinn; West, Keith P; Thorne-Lyman, Andrew
Abstract: Objectives: Study objectives were to identify the prevalence and risk factors associated with the newly revised WHO indicator of minimum dietary diversity (MDD) among children aged 6–23 months in 7 countries in East and Southern Africa and to identify shared risk factors of programmatic importance across countries. Methods: MDD was defined as having >5 of 8 food groups including breastmilk in the past 24 hours. We used Demographic and Health Survey data from four East African countries, (Ethiopia 2015, n = 2965; Tanzania 2015, n = 3170; Rwanda 2014, n = 1162; Uganda 2016, n = 4418) and three Southern African countries, (Malawi 2015–16, n = 4879; Mozambique 2011, n = 3339, and Zambia 2013–14, n = 3776). A total of 8 child, 16 maternal, 8 household and 3 community level characteristics were selected for investigation and tested for associations with MDD using univariable logistical regression models. Significant ( P < 0.05) variables were included in multivariable adjusted models. The sampling design of the original surveys was accounted for in all analyses. Results: The proportion of children reaching MDD was highest in Mozambique (27.4%) and lowest in Ethiopia (12.0%). Among four East African countries, common risk factors for not meeting MDD apparent across multiple countries included lowest wealth quintile (Adjusted OR [AOR] range: 2.04∼3.45, ref: highest), no formal maternal education, (AOR: 1.68∼3.30, ref: higher education than secondary), maternal age of 15–24y (AOR: 1.28∼1.59, ref: 25–34y), mothers not engaging in agriculture work (ref: agriculture) (AOR: 1.64∼3.30) and protective risk factors included older child age (AOR: 0.46∼0.71, ref:6–11 months) and weekly exposure to media (radio, tv or newspaper; AOR: 0.56∼0.68). Among Southern African countries, female household head (AOR: 1.25∼1.72) was positively and older child age (AOR: 0.53∼0.67; ref:6–11 months) negatively associated with not meeting MDD. Conclusions: Common risk factors were identified across countries and may help to inform policy and targeting of programs related to improving the quality of complementary feeding in the region. Funding Sources: None.